Biological assays and theoretical density functional theory calculations of Rh(I), Ir(III), and Ru(II) complexes of chiral phosphinite ligand. (12th March 2020) - Rafikova, Khadichakhan; Binbay, Nil Ertekin; Meriç, Nermin; Kerimkulova, Aygul; Zazybin, Alexey; Binbay, Veysel; Okumuş, Veysi; Kayan, Cezmi; Işik, Uğur; Arslan, Nevin; Aydemir, Murat
Abstract : Four metal complexes, IL‐OPPh2 ‐Ru‐ p ‐cymene (3), IL‐OPPh2 ‐Ru‐benzene (4), IL‐OPPh2 ‐Ir‐Cp* (5), IL‐OPPh2 ‐Rh‐COD (6), have been evaluated for in vitro antioxidant activity such as 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging and reducing power activity. Maximum scavenging activity (71.43%) was obtained with IL‐OPPh2 ‐Ru‐ p ‐cymene, whereas IL‐OPPh2 ‐Rh‐COD showed the highest reducing power ability. The complexes were also studied for their antimicrobial activity against three Gram‐positive and three Gram‐negative bacteria. In addition, DNA binding of the complexes was evaluated using calf thymus DNA. Both Ru(II) complexes exhibited good DNA‐binding activity while the other complexes did not have any activity. Furthermore, ab initio quantum calculations of four complexes were also carried out using density functional theory to better understand their chemical behaviors. Abstract : A chiral phosphinite ionic liquid (IL‐OPPh2 ) and its metal complexes (IL‐OPPh2 ‐Ru‐p‐cymene, ILOPPh2 ‐Ru‐benzene, IL‐OPPh2 ‐Ir‐Cp*, IL‐OPPh2 ‐Rh‐COD weresynthesized. The complexes have been evaluated for in vitro antioxidantactivity such as DPPH radical scavenging and reducing power activity. Maximumscavenging activity (71.43%) was obtained with (IL‐OPPh2 ‐Ru‐p‐cymene. In addition, DNA binding ofthe complexes was evaluated using Calf Thymus DNA. Furthermore, Ab‐initio quantum calculations of four complexes were also carried outby using Density Functional Theory (DFT), to better understand their chemical behaviors.please proceed accordingly. Highlights: The coordination of IL‐OPPh2 toward a variety of transition‐metal centers has been studied. Free radical scavenging, reducing power, antibacterial activity, and DNA binding were studied. Maximum scavenging activity (71.43%) was obtained with IL‐OPPh2 ‐Ru‐p‐cymene. Both Ru(II) complexes exhibited good DNA‐binding activity. Ab initio quantum calculations of the complexes were also carried out using density functional theory.